“Together on the Way”: Occupational Therapy in Mainstream Education—A Narrative Study of Emerging Practice in Switzerland - Angelika Echsel; Lee Price; Staffan Josephsson; Christina Schulze (Occupational Therapy International)
In Switzerland, recent changes in legislation have reformed special needs education; more children with special needs are now integrated into mainstream schools. Health professionals such as occupational therapists are not embedded in the Swiss education system, but pediatric occupational therapists are starting to work at schools, with the aim of enabling children’s full participation as school students. This is bringing a change to the practice of pediatric occupational therapists. Cultural, political, and social factors differ in many ways from those of other countries where most of the current research on pediatric occupational therapists in mainstream education has been conducted. The need for school-based research that is situated within the political, structural, and cultural context of a country has been stressed in different studies. This qualitative study employed narrative analysis to explore the practice experiences and clinical reasoning of Swiss pediatric occupational therapists when working with children with special needs in the school context. Three main themes were identified in the narratives: “bringing in an occupational therapy perspective,” “focusing on school-related occupations,” and “collaborating with different inclusion players.” These represent three different aspects of the therapists’ emerging practice. The participants highlight different approaches for children with special needs to enable their participation in everyday life at school through learning, playing, and being with their peers. The findings are discussed in relation to current international research and with respect to European countries with a similar political and structural context, thus complementing approaches to school-based occupational therapy.